Kenya : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2010)
The Medium Term Plan (MTP) identifies the key policy actions and reforms, as well as programs and projects that the Grand Coalition Government in Kenya intends to implement. The overall objective is to realize a higher and sustainable growth of the economy in a more equitable environment, accompanied by increased employment opportunities. The MTP aims at increasing real GDP growth. The financial services sector will play a key role in mobilizing the savings and investments required to implement the MTP.